Socio-Demographic and Clinical Profiles of End-Stage Renal Disease Patients Undergoing Haemodialysis in Gaborone, Botswana (Tanzania Medical Journal, 2021)
BackgroundChronic kidney disease has been on the rise worldwide as well as in sub- Saharan Africa. End-stage renal disease (ESRD) is a major public health problem worldwide and is associated with significant morbidity and mortality. There is a dearth of data on the epidemiology of ESRD patients on renal replacement therapy in sub-Saharan Africa including Botswana.AimTo describe the socio-demographic and clinical profiles of ESRD participants on haemodialysis by gender and HIV status in Botswana.MethodsA cross sectional study involving participants undergoing maintenance haemodialysis in three centers was conducted between February and June 2019. Data was analysed using Stata 14 statistical software. Chi-square test, Fisher’s exact test and t-test were used to determine association between socio-demographic/clinical characteristics and gender/HIV status.ResultsOverall, 107 participants were enrolled and 65.4% were males. Their mean age± standard deviation at the time of initiation of haemodialysis was 47.5+13.0 years. The prevalence of HIV-infection, diabetes mellitus and hypertension were 24.3%, 26.2% and 90.7%, respectively. The regular use of traditional medicine was ascertained in 43.9% of participants. HIV-infection was significantly associated with hypertension (p=0.04) and low body mass index (p<0.01). Reported use of traditional herbal medicine was a significant associated factor among males (p= 0.01). Unemployment rate among participants was 41.1%, with 54.5% of these participants attributing their unemployment to ill health, with women significantly more affected than men (p=0.04).ConclusionHypertension was the most common associated factor among our study participants. Participants on maintenance haemodialysis in our study were mostly males. Traditional herbal medicine use was significantly more common in men whereas female participants appeared to have higher prevalence of obesity compared to male counterparts. HIV-infected participants were significantly more likely to have low body mass index and be hypertensive. Women were significantly more likely to be unemployed due to ill health as compared to men. Prospective studies with large sample sizes are recommended to help understanding the role of individual associated factors in causing ESRD in Botswana and similar settings in sub-Saharan Africa.